Investigation of nitrogen pollutants transformation and its pathways along the long-distance prechlorinated raw water distribution system. (September 2020) - Shen, Zhen; Wang, Yueting; Chen, Wei; Xu, Hang; Zhang, Lei; Lin, Chenshuo; Lin, Tao; Tao, Hui; Mei, Caihua; Lu, Chunhui
Abstract: Understanding the transformation pattern of nitrogen (N) pollutants and its pathways in the prechlorinated raw water distribution system (PRWDS) is vital for controlling the stablitiy and safety of raw water qulity. This study investigated the N transformation, N functional genes and their correlations to find the N transformation pathways along the PRWDS. Results suggested that simultaneous nitrification, anaerobic ammonium oxidation and denitrification (SNAD) contribute to the N transformationin the PRWDS. Along the pipeline, anammox 16S rRNA (9.18 × 10 7 –8.41 × 10 8 copies/g), limited by prechlorination, was the most abundant N functional genes and anammox process was the main pathway of ammonia nitrogen (NH4 + -N). The decreasing NH4 + -N was connected with Planctomycetes, Nitrospira and abundance of nxrA attributing to the joint effort of anammox and declined nitrification. The concentration of nitrate (NO3 − -N) increasing at first and then decreasing, was correlated positively with Sphingomonas. because of the declined nitritication and increased denitrification. Besides, the NO3 − -N→NO2 − -N process was considered to be primary NO3 − -N transformation pathways. Increases in the concentration of dissolved organic nitrogen (DON) and nitrite (NO2 − -N) observed in the PRWDS had positive correlation with relative abundance of Pseudomonas . We believe that prechlorination shaped the particular bacterialcharacteristics in biofilms and influenced the N transformation pathways indirectly, resulting in the varying N transformation rules in PRWDSs. Moreover, systematic and extended research is particularly vital for determining the effects of changes in source water quality and environmental conditions on bacterial community structure and N conversion along PRWDSs. Graphical abstract: Image 1 Highlights: Nitrification, denitrification and anaerobic ammonium oxidation presented simultaneously in the PRWDS. The quantitive abundance of anammox 16S rRNA dominated among the N functional genes and was limited by chlorine. Anammox was the main NH4 + -N transformation pathway. The first step of denitrification was the key NO3 - -N transformation pathway.